2023
DOI: 10.1002/acr.25053
|View full text |Cite
|
Sign up to set email alerts
|

A Narrowing Mortality Gap: Temporal Trends of Cause‐Specific Mortality in a National Matched Cohort Study in US Veterans With Rheumatoid Arthritis

Abstract: Objective To examine temporal trends in all‐cause and cause‐specific mortality in patients with rheumatoid arthritis (RA) in the Veterans Health Administration (VHA). Methods We conducted a matched cohort study in the VHA from January 1, 2000 to December 31, 2017. Incident RA patients were matched up to 1:10 on age, sex, and VHA enrollment year to non‐RA patients, then followed until death or end of study period. Cause of death was obtained from the National Death Index. Multivariable Cox regression models str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…18,29 We found that patients with RA had an increased risk (AHR, 1.26; 95% CI, 1.04-1.54) of AS-related death, a mortality risk similar to that of ischemic heart disease in previous RA cohorts. 8,27 These data support a more severe AS disease course in contrast to a smaller study that reported similar AS progression rates in patients with RA and control patients, although that study had a shorter follow-up time and did not examine clinical AS outcomes. 30 The findings from the present study emphasize that valvular heart disease may be an underrecognized contributor to the persistent CVD-related mortality gap in RA, 8 particularly given the lack of improvement in ASspecific risk over time.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…18,29 We found that patients with RA had an increased risk (AHR, 1.26; 95% CI, 1.04-1.54) of AS-related death, a mortality risk similar to that of ischemic heart disease in previous RA cohorts. 8,27 These data support a more severe AS disease course in contrast to a smaller study that reported similar AS progression rates in patients with RA and control patients, although that study had a shorter follow-up time and did not examine clinical AS outcomes. 30 The findings from the present study emphasize that valvular heart disease may be an underrecognized contributor to the persistent CVD-related mortality gap in RA, 8 particularly given the lack of improvement in ASspecific risk over time.…”
Section: Discussionmentioning
confidence: 72%
“…We found that patients with RA had an increased risk (AHR, 1.26; 95% CI, 1.04-1.54) of AS-related death, a mortality risk similar to that of ischemic heart disease in previous RA cohorts . These data support a more severe AS disease course in contrast to a smaller study that reported similar AS progression rates in patients with RA and control patients, although that study had a shorter follow-up time and did not examine clinical AS outcomes .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Moreover, patients in the ORAL Surveillance study [ 19 ] were all over 50 years and had at least one major cardiovascular risk factor (e.g., smoking) that increases their neoplastic risk. In the rheumatoid arthritis population, malignancy is a leading cause of death [ 40 , 41 ], especially in patients not undergoing immunosuppressive therapy [ 42 ]. Nonetheless, this is also supported by our finding on RA indications, which is the only subgroup confirming the slightly increased risk of cancer in patients undergoing tofacitinib vs. anti-TNF.…”
Section: Discussionmentioning
confidence: 99%